Management of lateral epicondylitis (tennis elbow) by local infiltration of platelet rich plasma an outcome study - Kumawat, Pradeep Kumar; Goel, Rajesh; Kumhar, Urmila; Parmar, Rahul; Sharma, Rajesh; Sharma, Bharat (International Journal of Research in Orthopaedics, 2020)
Background: Platelet-rich plasma (PRP) has been recently the emerging biological therapy in which a large pool of signals released from platelets producing a biological microenvironment for local and migrating cells for tissue regeneration. A prospective randomized observational study was done to assess the efficacy of autologous PRP injection in lateral epicondylitis of elbow. Methods: A total 100 patients of lateral epicondylitis were selected and treated from December 2015 to November 2017. VAS (visual analogue scale) and PRTEE (patient rated tennis elbow evaluation) scoring were used for clinical and functional assessment at pre-injection, 2nd week, 4th week, 3rd month and 6th month. Results: At the end of 6 months follow-up 61% patients were completely relieved of pain. 34% patients had mild pain that was significantly decreased (p value <0.0001) from mean VAS (75) and mean PRTEE (78.62) to mean VAS (6.05) and mean PRTEE (5.63). 5 patients were lost their 6 months follow-up. There was a significant increase in post intervention pain for few days in 70% patients. Recurrence rate of 0% was noted at the end of 6 months follow-up. Conclusions: An injection of PRP improves pain and function in patients suffering from lateral epicondylitis.